Blockade of TRPV2 is a Novel Therapy for Cardiomyopathy in Muscular Dystrophy - Yuko Iwata (International Journal of Molecular Sciences, 2019)
Muscular dystrophy and dilated cardiomyopathy are intractable diseases and their treatment options are very limited. Transient receptor potential cation channel subfamily V, member 2 (TRPV2), is a stretch-sensitive Ca2+-permeable channel that causes sustained intracellular Ca2+ increase in muscular cells, which is a pathophysiological feature of degenerative muscular disease. Recent reports have clarified that TRPV2 is concentrated and activated in the sarcolemma of cardiomyocytes/myocytes during cardiomyopathy/heart failure and muscular dystrophy. Furthermore, these reports showed that inactivation of TRPV2 ameliorates muscle dysgenesis to improve cardiac function and survival prognosis. Although TRPV2 is a potential therapeutic target for cardiomyopathy, there were no TRPV2 inhibitors available until recently. In this review, we introduce our recent findings and discuss the current progress in the development of TRPV2 inhibitors and their therapeutic applications for cardiomyopathy associated with muscular dystrophy.